Hak Milik dan Tanggung Jawab Sosial (Studi Tafsir Al-Quran) - Hafid, Abd Hafid; AbuBakar, Achmad; Irham, Muhammad (AL-IQTISHAD: Jurnal Ekonomi, 2025)
This research aims to analyze property ownership and social responsibility. Through a thematic exegetical approach (tafsir maudhui), this research examines the status of wealth in the Qur'an, the concept of wealth ownership in the Qur'an, and the implementation of property rights as a form of social responsibility. The research findings indicate that 'Mal' (wealth) is mentioned in the Qur'an, with its various derivations, 87 times. Wealth (al-Mal) itself is defined as anything that possesses legal and concrete (a'in) value, is generally desired by human nature, can be owned, stored, and utilized. Islam views wealth as something highly important in human life, to the extent that Sharia designates it as one of the five essential matters that must be fulfilled, protected, and considered to realize human well-being in this world and the hereafter; property ownership, based on the Qur'anic concept, manifests as wealth for economic activity, as an indicator of collective welfare, and includes prohibitions against hoarding and consuming wealth unjustly. A Muslim who possesses wealth is commanded to help others as a form of social responsibility. Islamic teachings command its adherents to disburse a portion of their wealth in the form of zakat, infaq, and sadaqah.This research recommends that everyone distribute a portion of their wealth according to the guidance of the Qur'an. Zakat, infaq, and sadaqah, disbursed as a form of social responsibility, reflect humanity's chosen role in managing the wealth entrusted by Allah SWT.